Sport Reservation System With Decision Support System Features For Sport Complex of Universiti Utara Malaysia - Al-Habeeb, Talal Talib Jameel (2008)
This project presents a web based study highlighting the best practices in designing and building a prototype. It used web-based application in a system which includes both an online reservation system for the sport activities, and DSS to help the manager of the sport complex. This project used object-oriented analysis and design (OOAD) methodology, and UML in designing and developing a prototype. JSP and MYSQL etc. provided adequate support for building a prototype. After developing the prototype, evaluation of it has been done by using usability testing through the distribution of questionnaires on a sample of users including the students and staff. An interview has been held also with the manager of the sport complex in UUM. The responds from the users show that our objectives have been met in this study. We concluded that online sport reservation system provides an opportunity to the users to be familiar with the web applications, and provides enhancement to the management of the sport complex through the use of a data-driven decision support system.